Incidence of Lower Urinary Tract Symptoms in Middle Aged Patients Visiting the Gynaecology Out Patient Department of Shalamar Hospital, Lahore, Pakistan - Nazli Hameed; Asma Shahnawaz; Muhammad Asghar Ali; Aleezay Asghar (Shalamar Medical & Dental College, Lahore, Pakistan, 2019)
Objective: To determine the incidence of Lower Urinary Tract Symptoms (LUTS) among patients visiting the gynaecology Outpatients Department (OPD) of Shalamar Hospital. Material & Methods: A cross sectional study was performed and 300 patients were recruited. Patients aged 40 to 60 years, visiting the Gynaecology OPD at Shalamar Hospital, Lahore were enrolled from 1st February 2018 to 30th September 2018. The participants were categorized in to two sets: Premenopausal (n=187) and Post-Menopausal (n=113). They were asked to fill the international Consultation and Incontinence Questionnaire-Short Form (ICIQ-UI Short Form). Results: Increased urinary frequency was found to be the most commonly reported symptoms (48%).Stress incontinence and urge incontinence were reported by 58% subjects amongst postmenopausal category and 42% in the premenopausal category. Presence of LUTS was observed to be directly proportional with age. Conclusion: A high incidence of LUTS was observed among patients visiting gynaecology OPD of Shalamar Hospital, Lahore. Risk factors of LUTS and incontinence, like obesity and multiparity were frequency reported. Further studies are required to understand the magnitude of this problem in general population of Pakistan.